Phone-Based Smart Home System - Ganaeson, Moganapriya; Mohd Hezri Bin Mohd Lwi @ Mokhtar (Progress in Engineering Application and Technology, 2023)
Phone-Based Smart Home System is a type of wireless communication that can be used at home to remotely control household equipment. This project’s purpose is to create a foundation for building a wireless communication that can be used at home to control household equipment remotely.[3] The objective that is stated and trying to achieve in this project is to design and develop a voice control system by developing a system with a microcontroller that controls the switching of electrical appliances such as the light, fan, and door. The Bluetooth communication was designed with the Android Bluetooth Control application where the interface is combined with the Arduino Uno and connected with the relay module.